Pacific affairs - Institute of Pacific Relations (Institute of Pacific Relations, 1928)
Includes book reviews and bibliographies.
Keywords: Pan-Pacific relations : Periodicals; Relations panpacifiques : Périodiques; Pan-Pacific relations; Politique étrangère; Relations internationales; PACIFIC OCEAN REGION; ASIA; PAN-PACIFIC RELATIONS; Asie; Pacifique (Région)